A 8-b-Precision 6T SRAM Computing-in-Memory Macro Using Segmented-Bitline Charge-Sharing Scheme for AI Edge Chips - Su, Jian-Wei; Chou, Yen-Chi; Liu, Ruhui; Liu, Ta-Wei; Lu, Pei-Jung; Wu, Ping-Chun; Chung, Yen-Lin; Hong, Li-Yang; Ren, Jin-Sheng; Pan, Tianlong; Jhang, Chuan-Jia; Huang, Wei-Hsing; et al. (IEEE journal of solid-state circuits, 2023)
Advances in static random access memory (SRAM)-CIM devices are meant to increase capacity while improving energy efficiency (EF) and reducing computing latency ( T_{AC} ). This work presents a novel SRAM-CIM structure using: 1) a segmented-bitline charge-sharing (SBCS) scheme for multiply-and-accumulate (MAC) operations with low energy consumption and a consistently high signal margin across MAC values; 2) a bitline-combining (BL-CMB) scheme to reduce the number of analog-to-digital converters (ADCs) and, thereby, provide options in determining a tradeoff between EF and inference accuracy; 3) a source-injection local-multiplication cell (SILMC) connected to two types of global-bitline-switch to support the SBCS and BL-CMB schemes with consistent signal margin against process variation in transistors; and 4) prioritized-hybrid ADC to suppress area and power overhead for analog readout operations. We fabricated a 28-nm 384-kb SRAM-CIM macro using foundry-provided compact-6T cells supporting MAC operations with 16 accumulations of 8-b input and 8-b weight with near-full precision output (20 b). This macro achieved T_{AC} of 7.2 ns and EF of 22.75 TOPS/W performing 8-b-MAC operations.